Thermal evaluation and simulation of glass wool/maerogel blanket - Jamnani, Bahador Dastorian (2014)
Aerogel blankets are composites of silica aerogel particles dispersed in a reinforcing fiber matrix that turns the brittle aerogel into a durable and flexible insulating mat. While aerogel blanket manufacture from either organic or inorganic material, they are still some concerns over current environmental issues which are common worldwide are global warming, greenhouse effect, and climate change. Awareness of this environmental concern has led to the rise in an effort to renew agricultural waste like RHA (rice husk ash) which is cheaper precursor or a simple method in ambient pressure. As part of this study, to produce an insulator; glass wool was modified by ambient pressure drying methods to fabricate the flexible aerogel blanket. In order to evaluate thermal resistance of aerogel blanket, a hot plate is used. The microstructure of these aerogel blankets are also investigated for better understanding of the production process. Knowledge of the thermo-mechanical properties is important for the optimization of the design for these heterogeneous materials. In order to assess the aerogel blanket, some technics such as thermal gravimetric analysis (TGA), scanning electron microscopic (SEM) and Fourier Transform Infrared spectrum (FTIR) was done. Moreover a simple numerical micro model have been developed to predict the effective thermal conductivity of flexible aerogel blankets, which consist of fibers, aerogel particles and air-pockets. This simulation has two parts. In the first part of simulation, the effective thermal conductivity of the aerogel composites is computed with different aerogel particles and different volume ratios using the finite element method. The numerical analysis of thermal conductivity is conducted by generating 3D models of the microstructure of the aerogel blanket. In the second part of model, the extracted result from the micro model is inputted to the real sized model to predict top surface temperature. Finally all experiment data are validated by a numerical real sized model. In this study, a flexible aerogel blanket shows very good thermal resistance compare to original glass wool which is around 35% improvement. In addition TGA reveals that Maerogel® can retard material decomposition of blanket from 270°C to 287°C. Moreover SEM and FTIR clearly show that there is a good bonding between SiO2 particles that make a strong network to tolerate high temperature and to be flexible blanket. Furthermore Maerogel® blanket structurally was simulated then was validated by experiment result that showed good agreement; there is a well matching between the data that were extracted from simulation and experiment.